Yeast Detection in Mango Flavored Kefir from Small Scale Manufacture in Semarang, Central Java, Indonesia - Ahmad Ni'matullah Al-Baarri; Dian Ari Setianingsih; Yoyok Budi Pramono (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2020)
This research was done to detect total yeast on small scale kefir industry in Semarang, Central Java, Indonesia. The total plate count method was used to analyze total yeast in mango flavored kefir. This research used mango flavored kefir since this products was the top demand by consumer among kefir flavored products that was produced in this manufacture. Kefir from manufacture was transferred to laboratory using container box to provide buffer in the temperature decrease. As result, total yeast in mango flavored kefir was 1,21±0,06x105 CFU/ml. This total yeast was in the range of the Standard Codex 243-2003 which required a minimum total of 104 CFU/ml. The 1 log unit differences should provide the awareness to manufacture to maintain kefir in low temperature to minimise the multiplication of total yeast resulting the appearance of unwanted flavor. As conclusion, the mango flavored kefir was analyzed in total yeast successfully and in the range of Standard Codex of kefir